MATERNITY AND CHILDREN’S HOSPITAL IN JEMBER REGENCY WITH A BIOPHILIC CONCEPT AND SMART BUILDING APPROACH - Lenata Vahzeilan; Nurhamdoko Bonifacius; Raqyan Mas Bimatyugra Jati (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
Maternal and child health is a crucial aspect of social development and community well-being. Jember Regency, as one of the regions with high maternal mortality (MMR) and infant mortality (IMR) rates, requires optimal and well-integrated healthcare facilities. Therefore, the Nurtura Maternity Hospital design project is proposed as a solution to provide holistic and innovative healthcare services. The main concept of this hospital design is the biophilic design approach, which integrates natural elements into the building environment to create a healthier, more comfortable atmosphere and accelerate the patient healing process. The design considers the placement of environmental sensors, automatic lighting systems, and smart ventilation that are harmoniously integrated with the building’s structure and aesthetics. The outcome of this design is expected to serve as a model maternity and children’s hospital that not only delivers high-quality medical services but also creates a healthy, comfortable, and sustainable healing environment.